(untitled) (Innovaciones Educativas, 2025)
This study aimed to determine whether classroom teaching in the subject of Biology incorporates contextualization and everyday relevance of content, particularly in relation to the environmental theme proposed by the Ministry of Public Education (MEP) of Costa Rica. This objective responds to the need to enhance students’ prior knowledge by recognizing their environment and lived experiences as key components of meaningful learning. Connecting curriculum content to students’ realities supports the construction of more relevant and applicable knowledge, fostering deeper understanding and ownership of biological concepts in daily life. The research followed a quantitative approach, which enabled the documentation of how student context and experiences were integrated into the teaching of the environmental theme. It considered how factors such as geographic origin and educational modality influence the teaching and learning of Biology. The sample included 400 students and 60 teachers who participated in the 2023 Costa Rican Biology Olympiad. This population was selected because it represents students from across the country and from diverse educational modalities, allowing for a broader interpretation of the research objective. First, students completed a cognitive test related to the environmental theme. This was followed by questionnaires for both teachers and students, which included concrete examples of the curriculum content to assess whether these were taught in connection with students’ contexts and lived experiences. Data analysis included Chi-square tests and ANOVA to explore relationships between cognitive test results, questionnaire responses, geographic origin, and educational modality. The findings indicate that both geographic origin and educational modality significantly influence the degree of content contextualization.